Differences between programming languages offered by the academy versus demanded by the companies in Costa Rica: Information Systems Engineering from the Universidad Nacional - Quesada Rosales, Ariella (2017)
This article presents the results of an investigation that aims to analyze the differences between programming language required by companies in the Costa Rican labor market versus current programming languages offered by the academy. It also shows the main factors to consider new graduates in this specific area of information and communication technologies to be hired. The study finds that there is a consistent relationship between the major programming languages taught at universities and request by companies that corresponds to management Java, C++, C#, Javascript and PHP.